Rheological, Morphological and Mechanical Characterization of Recycled Poly (Ethylene Terephthalate) Blends and Composites - Pereira,Laurenice Martins (2017)
This study evaluated the effect of adding poly (ethylene methyl acrylate) (EMA) and cotton linter (CL) on the properties of recycled poly (ethylene terephthalate) (PETrec). For this, PETrec/EMA blend and PETrec/EMA/CL composite were developed. In order to improve the interfacial adhesion and the properties of these materials, ethylene/methyl acrylate/glycidyl methacrylate terpolymer (EMA-GMA) and polyethylene-grafted maleic anhydride (PE-g-MAH) were added. The rheological results showed that the addition of EMA increased and the addition of 1 wt% of CL reduced the viscosity. The morphological analysis of the non-compatibilized blend and composite showed poor interfacial adhesion. Polymer blends with 2 and 6 wt% of EMA had better mechanical properties, since these formulations have the smallest average particle diameter of 0.58 and 1.00 µm, respectively. The mechanical testing of composites showed a material with higher maximum strength and elasticity modulus than polymer blend when analyzed at the same EMA phase concentration. The use of EMA-GMA was effective in reducing the size of particles of the EMA in the blend.